Exploring New Zealand management attitudes to customer involvement in new product development in the health supplement industry - Zhang, Yan (Auckland University of Technology, 2009)
New product development (NPD) is seen as one of the most important business strategies that are widely undertaken by many firms. It is a very effective and efficient way to satisfy the expectations of customers. However, current customers’ expectations are changing fast, as well as being difficult to define. Therefore, involving customers in the actual process of new product development is becoming more popular. Customer involvement is an important and effective way for firms to gain knowledge of customers more easily, especially knowledge of their needs and what will satisfy those needs. In the New Zealand health supplement industry, the competition is intense and the market environment is complex and unpredictable. Thus, based on the established theoretical literature of Cooper’s (2001) seven-stage NPD processes and Baxter’s (2007) six-dimension evaluation framework of NPD success, the main aim of this study is to create an in-depth understanding of customer involvement in the process of NPD. Also this study determines at which stages are customers involved in NPD in the New Zealand health supplement industry. In addition, this research will explore the understanding of the key determinants of NPD success and key factors of NPD success evaluation in the New Zealand health supplement industry. In this study, the multiple case studies technique was employed as the main empirical research method. In addition to the case studies, several sources were used for secondary data collection, such as the AUT online database and business articles. For the primary data collection the purposive sampling method was used to investigate six companies in the New Zealand health supplement industry, by interviewing the product development manager, general manager or CEO of each of companies. The collected data from interviewees in those six companies was analyzed using the technique of pattern matching. The findings of this research suggest that the key determinants of NPD success include market knowledge, product knowledge and relationships that must be considered by firms. In other words, knowledge of the market and product and their relationships are very important for firms to plan and operate a successful NPD project. The study also suggests that firms should involve customers in the NPD process, because customers can significantly contribute to NPD success. By analyzing the data from six interviews, and integrating this with information from the literature, the most important and effective factors that lead to success are found in New Zealand health supplement industry. These factors are financial success, market success and strategic advantage gains. Secondly, Cooper’s (2001) seven-stage NPD process model (which contains discovery, idea screening, scoping, business analysis, development, market testing and validation, and launch) and Baxter’s six-dimension NPD success evaluation framework (financial success, market success, technical success, speed to market, strategic advantage gains, and social and ecological sensitivity) were used and tested in this research, which is discussed based on the primary data. The results of the research suggested that there is only a slight difference in the initial stages of the NPD process in the New Zealand health supplement industry compared with Cooper’s (2001) seven-stage NPD process, and that Baxter’s (2007) six-dimension NPD success evaluation framework is supported in practice. This research also presents a number of implications from both strategic and managerial perspectives. From the strategic perspective, the findings suggest that successful NPD is very important for business survival and development. Further to this, customer involvement is vital for NPD success. Financial success, market success and strategic advantages gains were found to be the most important factors for the evaluation of NPD success. This research suggests that managers need a clear understanding of the factors that drive NPD success and knowledge of how to involve customers in NPD, and how to assess the success of NPD in terms of its outcomes.
Keywords: Customer involvement; Multiple case studies